2020
DOI: 10.1177/1077546320960995
|View full text |Cite
|
Sign up to set email alerts
|

Predictive-based sliding mode control for mitigating torsional vibration of drill string in the presence of input delay and external disturbance

Abstract: Dealing with torsional vibrations and stick–slip oscillations of a drill string system is a challenging engineering task in the oil drilling process because of the harmful and costly consequences of such vibrations. In this article, the drill string system is modeled using a lumped-parameter model with four degrees of freedom, and the bit–rock contact is represented by a nonlinear function of a bit velocity. Also, tracking the desired velocity of a drill string system with known constant input delay is address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…To verify the control results obtained in this work, in this section, a comparison with the results that was reported by Sadeghimehr et al(2020) -Castro, 2009). The authors applied the Smith-predictor-based SMC approach (SPSMC) in order to regulate the bit angular velocity in a constant speed.…”
Section: Verification and Comparison Of Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…To verify the control results obtained in this work, in this section, a comparison with the results that was reported by Sadeghimehr et al(2020) -Castro, 2009). The authors applied the Smith-predictor-based SMC approach (SPSMC) in order to regulate the bit angular velocity in a constant speed.…”
Section: Verification and Comparison Of Resultsmentioning
confidence: 78%
“…They incorporated two control schemes, cascade and decentralized control algorithms based on error compensation methods. There are other researches (Fubin et al, 2010; Karkoub et al, 2010; Navarro-López and Licéaga-Castro, 2009; Sarker et al, 2012; Sadeghimehr et al, 2020; Shi et al, 2011; Ritto and Ghandchi-Tehrani, 2019) in which the drill-string has been modelled by a multi degrees-of-freedom lumped model. Although the lumped model can provide a simple benchmark to understand the system, and accordingly, design a controller, it fails to accurately model its inherent nonlinear behavior, which in severe cases leads to dynamic errors.…”
Section: Introductionmentioning
confidence: 99%
“…Also, among the adopted advanced active control approaches is the sliding mode control approach (SMC) because it is a robust control method that can accommodate the effects of uncertainty of the drill-string parameters and reject the adverse effects of external disturbances. The SMC controller has been reported by Navarro-Lopez and Cortes [3] , Vaziri et al [4] , and Sadeghimehr et al [5] . It has been demonstrated that the method has effectively eliminated the stick-slip vibrations both theoretically and experimentally.…”
Section: Issue Ersion Imentioning
confidence: 97%
“…Mohammad Javad Moharrami et al conducted a nonlinear analysis of the drill pipe under the state of stick-slip vibration, and proposed a finite element (FE) modeling method for the full drill string, and established a limited three-dimensional nonlinear FE model that can evaluate the entire response of the drill pipe system under different operating conditions [12]. Roya Sadeghimeh et al proposed a sliding mode control algorithm based on the Smith predictor and studied the effect of delay parameters on system output [13]. Vahid Vaziri et al made a parametric analysis of a sliding mode controller that can suppress stick-slip vibration.…”
Section: Introductionmentioning
confidence: 99%